2018
DOI: 10.1177/0886260518766431
|View full text |Cite
|
Sign up to set email alerts
|

Grief and Solidarity Reactions 1 Week After an On-Campus Shooting

Abstract: The impact of interpersonal violence extends beyond the victims and perpetrator(s). The purpose of this research was threefold: (a) to identify whether college students' very early reactions to an on-campus shooting were associated with well-known predictors of distress, (b) to examine whether grief and distress reactions were distinguishable in the early days following a shooting, and (c) to investigate whether a compassionate self-identity was uniquely associated with grief but not distress. Beginning just 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
1
8
0
1
Order By: Relevance
“…The association between PTG and quiet ego adds to the literature on the benefits of a eudaimonic perspective in coping with stress (cf. Wayment et al, submitted; study of adults coping with unemployment; Wayment and Silver, in press; study of college students coping with college shooting). Our results regarding quiet ego and PTG reinforce Bluth et al (2013) recommendation that therapists and other health-care professionals working with mothers coping with ASD-related stressors incorporate eudaimonic elements into interventions (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The association between PTG and quiet ego adds to the literature on the benefits of a eudaimonic perspective in coping with stress (cf. Wayment et al, submitted; study of adults coping with unemployment; Wayment and Silver, in press; study of college students coping with college shooting). Our results regarding quiet ego and PTG reinforce Bluth et al (2013) recommendation that therapists and other health-care professionals working with mothers coping with ASD-related stressors incorporate eudaimonic elements into interventions (cf.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, using national samples, reported generally consistent findings, but of a smaller magnitude than the current study’s findings. The larger magnitudes in this study might be partially explained by closer temporal and physical proximity of students to the event, because physical proximity to or social distance from traumatic events influences their impact ( 2 , 5 ).…”
Section: Discussionmentioning
confidence: 84%
“…These findings show that a school shooting's effects extend beyond the school where it occurred. Students could have been influenced by factors such as degree of exposure, media coverage, number of victims known, and perceived similarity to victims, which have been associated with general distress and acute stress immediately following traumatic events (5).…”
Section: Discussionmentioning
confidence: 99%
“…Uczestnictwo w zbiorowym upamiętnianiu często staje się ważnym krokiem w aktywowaniu procesu żałoby, zapewnia bowiem osobom dotkniętym kryzysem bezpieczną przestrzeń do wyrażenia żalu i smutku. Społeczność skupia się wokół traumy, dzięki czemu proces upamiętniania jest "terapeutyczny" 32 i stanowi ważny zasób psychospołeczny w radzeniu sobie z przemocą 33 . Solidarność społeczna sprzyja zmniejszeniu symptomów depresji 34 , zaś wspierające środowisko zmniejsza prawdopodobieństwo wystąpienia PTSD 35 .…”
Section: Pomieszczanie żAłoby: Przestrzeń Miejska Jako Scena Spontaniunclassified